Isolation and identification of the main carotenoid pigment from a new variety of the ridgetail white prawn Exopalaemon carinicauda. (15th December 2018) - Zhang, Chengsong; Su, Fang; Li, Shihao; Yu, Yang; Xiang, Jianhai; Liu, Jianguo; Li, Fuhua
Highlights: A rare orange-red mutant of body color in Exopalaemon carinicauda was found. Higher concentration of free astaxanthin was detected in the new variety. Free astaxanthin was proved to be responsible for the color variation. It provides an alternative source of natural astaxanthin. Abstract: The ridgetail white prawn ( Exopalaemon carinicauda ) is an important economic species in China. In order to know the molecular basis and evaluate the potential nutrition value of a new variety of this species with orange-red color, the main carotenoid pigments were extracted and identified through high performance liquid chromatography. It showed that higher concentration of free astaxanthin existed in the new variety which might cause the color variation. The concentration of total astaxanthin in muscle and waste of the new variety was 3.3 and 1.9 fold higher than that in natural prawn under the same culture condition ( P < 0.05). The predominant geometric and optical isomers of astaxanthin in muscle of the new variety were identified as all- trans and 3 S, 3 ′S astaxanthin. This is the first report of astaxanthin-enriched E. carinicauda, which also provides an alternative source of natural astaxanthin and the possibility for improving the nutrition value in this species.